Editorial: Update on Translational Neuroimmunology - Research of ISNI 2018 - Probert, Lesley; Quintana, Francisco J.; Bar-Or, Amit (Frontiers in Immunology, 2020)
With its roots firmly planted in the fields of CNS autoimmunity and infection, the rapidly growing field of neuroimmunology is branching out to include almost every area of neurophysiology and neurological disease to encompass brain development and function, psychiatric illnesses, inflammatory demyelinating diseases, cancer, infections and neurodegeneration of the central and peripheral nervous systems. The nervous system is also functionally intimately interconnected, via immune mechanisms, to multiple other processes and organ systems including systemic inflammation, gut microbiome, and chronic pain, to name a few. The scope of neuroimmunology and its implications for the understanding of human health and disease, from diagnosis through therapeutics, was highlighted during the 14th Congress of the International Society for Neuroimmunology (ISNI) 2018, and the associated 2nd Global Schools of Neuroimmunology (GSNI), held together in August 2018 in Brisbane, Australia. The richness of topics covered is further illustrated through the series of related articles presented in this special issue of Frontiers in Neurology entitled ‘Update on Translational Neuroimmunology Research of ISNI 2018’.